2016
DOI: 10.1177/0021998315623626
|View full text |Cite
|
Sign up to set email alerts
|

Graded epoxy-hard coal composites: Analysis of filler particle distribution in the epoxy matrix

Abstract: The aim of the work was to achieve assumed gradation of hard coal particles distribution in epoxy matrix and thus gradation of properties. It was done by proper selection of compounds composition and conditions of the gradation formation. The graded composites were produced using centrifugal casting. Two types of epoxy resins as a matrix and two types of hard coal of various granulation as a filler were used. Samples in the form of bushings with radial carbon filler gradation were produced by changing filler t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Kumar et al [51] reported manufacturing by casting and characterization of epoxy composites with up to 12.5 wt% wood particles. Centrifugal casting is a way to obtain gradation of the filler due to centrifugal forces as reported by Stabik et al [52]. They report that as well as the particle gradation occurs, gradation of properties occurs too which could be interesting from different standpoints (decorative, percolation thresholds in some parts, and so on.…”
Section: Introductionmentioning
confidence: 93%
“…Kumar et al [51] reported manufacturing by casting and characterization of epoxy composites with up to 12.5 wt% wood particles. Centrifugal casting is a way to obtain gradation of the filler due to centrifugal forces as reported by Stabik et al [52]. They report that as well as the particle gradation occurs, gradation of properties occurs too which could be interesting from different standpoints (decorative, percolation thresholds in some parts, and so on.…”
Section: Introductionmentioning
confidence: 93%
“…In recent years, composite materials have gained popularity due to their many advantages, such as their low density and the ease and economy of their production [1][2][3]. Polymer-based composite materials are defined as materials in which the matrix is a polymer material, and the filler is made of organic or inorganic particles that are immiscible with the polymer [4][5][6][7]. Researchers around the world have taken steps to improve the operational properties of this group of materials by using various types of reinforcements, e.g., fibers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%